Superconductivity in a chiral nanotube - F. Qin (Nature Portfolio, 2017)
Chirality affects many properties of materials, but how it affects superconductivity remains unclear. Here, Qinet al. report nonreciprocal supercurrent flows in individual nanotubes of WS2via ionic gating, evidencing chiral superconducting transport.